SAT0001 Lack of obesity-related features in adipocytes and inflammatory cells in the infrapatellar fat pad (IFP). (15th June 2017) - Ioan-Facsinay, A; Jong, A de; Klein-Wieringa, I; Andersen, S; Kwekkeboom, J; Toorn, L Herb-van; de, B Lange-Brokaar; Delft, D van; Garcia, J; Wei, W; Heide, H van der; Bastiaansen-Jenniskens, Y; et al.
Abstract : Background: Obesity is associated with the development and progression of osteoarthritis (OA), both for weight-bearing and non-weight bearing joints. Several lines of research indicate that obesity-related systemic factors, such as adipose tissue-derived factors, could be involved in this association. The infrapatellar fat pad (IFP) is an adipose tissue depot localized in the knee joint. and could mediate obesity-associated effects. However, it is currently unknown whether and how obesity affects IFP. Objectives: To investigate the presence of obesity-related features in adipocytes and infiltrating immune cells in the IFP of OA patients. Methods: Knee OA patients (N=155: 68% women, mean age 65 years, mean (SD) BMI 29.9 kg/m 2 (5.7)) were recruited: IFP volume was determined by MRI in 79 knee OA patients, while IFP and subcutaneous adipose tissue (SCAT) were obtained from 106 patients undergoing arthroplasty. Crown-like structures (CLS) were determined using immunohistochemistry. Adipocyte size was determined by light microscopy and histology. Stromal vascular fraction (SVF) cells were characterized by flow cytometry. Results: IFP volume (mean (SD) 23.6 (5.4) mm 3 ) was associated with height, but not with BMI or other obesity-related features such as waist circumference, fat percentage and waist to hip ratio. The volume of IFP adipocytes did not correlate with BMI, in contrast to SCAT adipocytes. Few CLS were observed in IFP and their number did not differ between individuals with high and low BMI. Moreover, high BMI was not associated with higher infiltrating immune cell numbers in IFP, nor with changes in immune cell populations. Likewise, no molecular differences were observed in FCM-secreted factors between high and low BMI, except for an increased TNFa secretion in obesity. Since obesity is usually associated with a shift towards pro-inflammatory macrophages in conventional adipose tissue, we have extensively characterized IFP macrophages. Surprisingly, CD206 and CD163, usually associated with an anti-inflammatory phenotype were the most abundantly expressed surface markers on macrophages (81% and 41% respectively). In contrast, cytokine profiles revealed a pro-inflammatory phenotype of the total macrophage population, with cells producing predominantly IL-6 and TNFα, but little IL-10. Interestingly, the CD163+ macrophages were bigger and had a more activated and pro-inflammatory phenotype than their CD163- counterparts. However, no association with BMI could be observed for different macrophage populations or their cytokines. Conclusions: BMI-related features usually observed in SCAT and visceral adipose tissue could not be detected in IFP of OA patients, a fat depot implicated in OA pathogenesis. Disclosure of Interest: None declared